2020
DOI: 10.3390/su12072614
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Modified College Impact Model to Understand Chinese Engineering Undergraduates’ Sustainability Consciousness

Abstract: The college impact model provides a valuable framework for explaining various college student learning outcomes. However, few quantitative studies have examined the effectiveness of college impact model in explaining engineering undergraduates’ sustainability consciousness, a critical learning outcome in engineering education. This study proposes a modified college impact model to test the structural links among curriculum experiences, sustainable agency beliefs, and engineering undergraduates’ sustainability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…In general, the extent to which knowledge influences pro-environmental behavior has received far less attention than attitudinal and normative influences, despite its central relevance to environmental education and decision making [25,26]. Primary studies have found mixed evidence for direct versus indirect relationships between knowledge and behavior in the environmental domain [25,[27][28][29]. Recently, Dietsch et al [17] argued that key to demonstrating a direct relationship is to measure knowledge as objective, verifiable knowledge rather than self-report evaluations of how much one thinks one knows about environmental issues (perceived environmental informedness) or how much one perceives an environmental issue to be a problem (problem awareness).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the extent to which knowledge influences pro-environmental behavior has received far less attention than attitudinal and normative influences, despite its central relevance to environmental education and decision making [25,26]. Primary studies have found mixed evidence for direct versus indirect relationships between knowledge and behavior in the environmental domain [25,[27][28][29]. Recently, Dietsch et al [17] argued that key to demonstrating a direct relationship is to measure knowledge as objective, verifiable knowledge rather than self-report evaluations of how much one thinks one knows about environmental issues (perceived environmental informedness) or how much one perceives an environmental issue to be a problem (problem awareness).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the acknowledged influence of education on student behavior (Brody & Ryu, 2006), students have received relatively limited attention in sustainability studies (Murray, 2018). Furthermore, much of the existing sustainability research tends to be descriptive in nature (Barth & Rieckmann, 2012), with few studies focusing specifically on the Asian continent (Kalsoom et al, 2017;Olsson et al, 2019;Zhao et al, 2020). This study aims to analyze the current level of sustainability awareness among university students, particularly examining the development of sustainability knowledge, attitudes, and behaviors, and exploring whether these behaviors are influenced by individuals' beliefs in their capacity to effect change.…”
Section: H1: Sustainability Knowledge Affects Sustainability Behaviormentioning
confidence: 99%
“…Several studies showed that holistic, multifaceted pedagogies did affect attitudes and values, potentially leading to clarification and shifts e.g., [94,107]. Others could not detect any effect of instructional practice on affective dimensions, e.g., [154], or found that "traditional" formats affected attitudes as well [155]. In sum, it seems that pedagogies inviting students to engage more deeply with a phenomenon, and particu- Many studies investigated the possible effects of specific pedagogies on knowledge and abilities and skills (Table 3; Table S3, Supplementary Materials, summarizes study results).…”
Section: What Should Be Learned In Hesdmentioning
confidence: 99%